(untitled) (Journal of Health Sciences, 2020)
Introduction: Work-related musculoskeletal disorders (WMSDs) represent a major problem for society, employers, and employees. These kinds of problems can cause discomfort, pain, and poor work performance. Among physiotherapists, the 1-year prevalence of WMSD ranges from 28 to 96%. Most problems occur in the lower back, with a 1-year prevalence of up to 83%. This study aimed to determine the prevalence of WMSD on a sample of physiotherapists from Slovenia and to identify associations between demographic/anthropometric variables, job satisfaction, and physical activity with WRMD aiming to contribute to the development of effective prevention and control strategies. Methods: The extended Nordic musculoskeletal questionnaire was used to obtain data from a sample of 102 physiotherapists. Data were presented with descriptive statistics and processing was performed with the Spearman’s rank correlation coefficient for non-parametric variables. The level of statistical significance was set as p ≤ 0.05. Results: The 1-year prevalence of WMSD was 92.2%. One-year prevalence of WMSD was highest for the neck (64%) and lower back (63%). Higher age and more years of practice were correlated with WMSD for shoulders and ankles/feet areas. Several patients treated by a physiotherapist were a risk factor for difficulties in the neck and multiple body areas. The level of physical activity was not correlated with WMSD in different body areas. Conclusion: The prevalence of WMSD found in our study sample was among the highest compared to other countries, despite probably having similar working conditions as elsewhere in Europe. The first WMSD of Slovenian physiotherapists mostly did not occur in the first 5 years of practice as other studies reported, which could be explained as a result of a good educational training of young physiotherapists. Possible reasons for the high prevalence of WMSD could be that our study sample represented only secondary and tertiary levels of health care; another reason could also be non-ergonomic and hard working conditions during their careers. Physiotherapists are mostly adequately physically active, however, that did not turn out to be effective WMSD prevention in our sample. The relatively high prevalence is indicating the need for better interventions and prevention of WMSD in Slovenian physiotherapists.